Tantangan Pendidikan Agama Islam dan Moderasi Beragama dalam Menghadapi Masyarakat Multikultural - Yanto, Masti; Abidin, Zeinal; Maizah, St.; Inayati, Mahfida (Medan Resource Center, 2023)
The dynamics of Islamic religious education and religious moderation are the focus of attention in facing today's multicultural society. The main challenge is to combine religious teachings with the values of moderation so that they can synergize with the diversity of cultures and beliefs. The prospect of inclusive and moderate Islamic religious education is capable of promoting interfaith dialogue and tolerance, forming individuals who have a deeper understanding of Islam, and minimizing the potential for radicalization. However, this approach faces obstacles such as resistance to change and diverse interpretations. The importance of developing relevant curricula, training competent teachers, and active participation of the entire community in Islamic religious education and religious moderation to achieve this goal. Also, Islamic religious education must reflect the values of tolerance and harmony in diverse communities within the scope of society.